Effect of irrigation regimes on growth, herbage and oil yields of lemongrass (Cymhopogon flexuosus) under semi-arid tropical conditions - SINGH, MUNNU; SHIVARAJ, B (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted for 2 years during the crop seasons of 1991-93 at Bangalore to study the effect of 6 irrigation regimes (1.60, 0.80, 0.50, 0.40 and 0.30 Irrigation Water: Cumulative Pan Evaporation ratio) along with the Control (no irrigation) on 3 lemongrass [Cymbopogon flexuosus (Steud.) Wats.] cultivars (’OD 19’, ’Pragati’ and ’Cauvery’). The moisture regime of 0.50 IW : CPE ratio gave significantly higher oil yield compared to 0.40, 0.30 and control and was at par with 0.80 and 1 .60. Plant height, no. of tillers/plant and leaf area index increased up to 0.80 IW : CPE ratio. Among the lemongrass cultivars ’Cauvery’ gave significantly higher oil content (0.78%) and oil yield (350 kg/ha).